2012
DOI: 10.1038/nclimate1507
|View full text |Cite
|
Sign up to set email alerts
|

Rising CO2 and increased light exposure synergistically reduce marine primary productivity

Abstract: Carbon dioxide and light are two major prerequisites of photosynthesis. Rising CO2 levels in oceanic surface waters in combination with ample light supply are therefore often considered stimulatory to marine primary production(1-3). Here we show that the combination of an increase in both CO2 and light exposure negatively impacts photosynthesis and growth of marine primary producers. When exposed to CO2 concentrations projected for the end of this century(4), natural phytoplankton assemblages of the South Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
294
10
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 329 publications
(325 citation statements)
references
References 32 publications
18
294
10
3
Order By: Relevance
“…Furthermore, whereas previous studies have demonstrated interactions between OA and high light, causing amplified high-light stress under shortterm exposure (Gao et al 2012b;Hoppe et al 2015), we did not observe such effects. In fact, prior to the dilution, we even observed decreasing electron transport and enhanced energy conversion efficiency (P max -ETR RCII and P max -J C /n PSII ; Table 4) with increasing pCO 2 under LL, hinting towards potentially beneficial OA effects under low irradiances (Rokitta and Rost 2012).…”
Section: Assemblages Did Not Respond To Ocean Acidificationcontrasting
confidence: 55%
“…Furthermore, whereas previous studies have demonstrated interactions between OA and high light, causing amplified high-light stress under shortterm exposure (Gao et al 2012b;Hoppe et al 2015), we did not observe such effects. In fact, prior to the dilution, we even observed decreasing electron transport and enhanced energy conversion efficiency (P max -ETR RCII and P max -J C /n PSII ; Table 4) with increasing pCO 2 under LL, hinting towards potentially beneficial OA effects under low irradiances (Rokitta and Rost 2012).…”
Section: Assemblages Did Not Respond To Ocean Acidificationcontrasting
confidence: 55%
“…), elevated CO 2 remarkably enhanced their growth [5,6], with their CO 2 concentrating mechanisms (CCMs) being down-regulated. In diatoms, similar trend has been reported under laboratory conditions (low light and constant temperature), however, under high levels of sunlight, the diatoms grow much slower under the OA treatment compared to ambient CO 2 condition [7]. Mechanistically, downregulation of CCMs under elevated pCO 2 can save energy for active uptake of inorganic C, the saved energy could be employed to stimulate growth under light-limiting condition and to exacerbate light stress under over-saturating light levels, leading to up-regulated photorespiration.…”
Section: Photosynthesis and Growthsupporting
confidence: 57%
“…Mechanistically, downregulation of CCMs under elevated pCO 2 can save energy for active uptake of inorganic C, the saved energy could be employed to stimulate growth under light-limiting condition and to exacerbate light stress under over-saturating light levels, leading to up-regulated photorespiration. That is, the changed carbonate chemistry due to OA is supposed to increase light stress, as indicated in enhanced nonphotochemical quenching (NPQ) in surface phytoplankton assemblages in the South China Sea [7]. Nevertheless, increased NPQ under OA do not always couple with decreased growth or photosynthetic carbon fixation [6].…”
Section: Photosynthesis and Growthmentioning
confidence: 99%
“…It is only under ideal conditions that there is a strong linear correlation between PSII photochemistry and photosynthetic carbon fixation (Genty et al, 1989), although in situ photochemical yield showed a good correlation with primary productivity (Kolber and Falkowski, 1993;Suggett et al, 2001). Increased carbon loss by photorespiration or respiration was found under high irradiance in HC-acclimated phytoplankton (Gao et al, 2012b;Yang and Gao, 2012). An increase in the water-water cycle (Asada, 1999) could also drain electrons from PSII without contributing to carbon fixation.…”
Section: Discussionmentioning
confidence: 99%